Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan - Azfa, Mohamad Farhan; Solihah, Riri Hilmatus (Journal of Information Systems and Management (JISMA), 2025)
Human resources is the greatest asset for the survival of the company, both for now and for the long term. Human resources is one thing that cannot be separated from the level of the business world and work, especially now that there is a lot of competition in the business world. This study aims to explain the influence of work motivation partially on employee performance, to explain the influence of the work environment partially on employee performance and to explain the work motivation and work environment simultaneously on employee performance. Based on the results of the analysis showed that work motivation has a significant effect on employee performance the research method this time is a quantitative research method presented in the form of narrative literature review. The conclusion of this study is that motivation and work environment have a positive and significant effect on employee performance, motivation and work environment explain the effect on employee performance variables by 65.3%. While the remaining 34.7% is the influence of other independent variables that are not studied in this study such as leadership, salary, work stress and so forth.